Pneumonia among Under-Five Children in Northwest Ethiopia: Prevalence and Predictors-A Community-Based Cross-Sectional Study - Zewudu Andualem; Tsegaye Adane; Abiye Tigabu; Walelign Worku Yallew; Sintayehu Daba Wami; Henok Dagne; Jember Azanaw; Gebisa Guyasa; Zelalem Nigussie Azene; Mastewal Endalew (Hindawi Limited, 2020)
Background. Acute respiratory infections in particular pneumonia constitutes the leading cause of morbidity and mortality among children under five years of age throughout the world. In Ethiopia, pneumonia continues to be the major childhood problem and killer, particularly in the study area. However, evidence dealing with the problem is still unavailable. The current study is aimed at determining the magnitude and risk factors of childhood pneumonia in Gondar City. Methods. A community-based cross-sectional study was employed in five randomly selected clusters/subcities of Gondar City. A total of 792 child-mother/caregiver pairs in the selected subcities/clusters were included. A pretested and validated questionnaire was used by trained supervisors through house-to-house visits to collect the data. Binary logistic regression (bivariable and multivariable) was employed. An adjusted odds ratio with 95% confidence interval was used to declare statistically significant variables on the basis of p<0.05 in the multivariable logistic regression model. Results. The prevalence of pneumonia among under-five children in the current study was found to be 12% with 95% CI: 10% to 14.4%. The presence of unpaved road within 100 m of the house (AOR=2.27, 95% CI: 1.41-3.66), living within 100 m of heavy traffic (AOR=1.94, 95% CI: 1.19-3.16), the habit of not opening doors while cooking (AOR=1.62, 95% CI: 1.01-2.62), the presence of cockroach infestation (AOR=1.98, 95% CI: 1.25-3.14), and new carpet in the house (AOR=1.75, 95% CI: 1.01-3.03) were statistically significant variables associated with childhood pneumonia. Conclusions. This study indicated that the prevalence of childhood pneumonia is still high. As such, enhancing strategies that would address unpaved roads within 100 m of the house, living within 100 m of heavy traffic, the habit of not opening doors while cooking, cockroach infestation, and new carpet in the house to reduce the burden of childhood pneumonia needs to be advocated.